Is Maximum Food Intake in Endotherms Constrained by Net or Factorial Aerobic Scope? Lessons from the Leaf-Eared Mouse - Maldonado, Karin; Sabat, Pablo; Piriz, Gabriela; Bogdanovich, José M.; Nespolo, Roberto F.; Bozinovic, Francisco (Frontiers in Physiology, 2016)
Food availability varies substantially throughout animals’ lifespans, thus the ability to profit from high food levels may directly influence animal fitness. Studies exploring the link between basal metabolic rate (BMR), growth, reproduction and other fitness traits have shown varying relationships in terms of both magnitude and direction. The diversity of results has led to the hypothesis that these relationships are modulated by environmental conditions (e.g. food availability), suggesting that the fitness consequences of a given BMR may be context-dependent. In turn, there is indirect evidence that individuals with an increased capacity for aerobic work also have a high capacity for acquiring energy from food. Surprisingly, very few studies have explored the correlation between maximum rates of energy acquisition and BMR in endotherms, and, to the best of our knowledge, none have attempted to elucidate relationships between the former and aerobic capacity (e.g., maximum metabolic rate [MMR], aerobic scope [Factorial aerobic scope, FAS; Net aerobic scope, NAS]). In this study, we measured BMR, MMR, maximum food intake (recorded under low ambient temperature and ad libitum food conditions; MFI), and estimated aerobic scope in the leaf-eared mouse (Phyllotis darwini). We, then, examined correlations among these variables to determine whether metabolic rates and aerobic scope are functionally correlated, and whether an increased aerobic capacity is related to a higher MFI. We found that aerobic capacity measured as NAS is positively correlated with MFI in endotherms, but with neither FAS nor BMR. Therefore, it appears plausible that the capacity for assimilating energy under conditions of abundant resources is determined adaptively by NAS, as animals with higher NAS would be promoted by selection. In theory, FAS is an invariant measurement of the extreme capacity for energy turnover in relation to resting expenditure, whereas NAS represents the maximum capacity for simultaneous aerobic processes above maintenance levels. Accordingly, in our study, FAS and NAS represent different biological variables; FAS, in contrast to NAS, may not constrain food intake. The explanations for these differences are discussed in biological and mathematical terms; further, we encourage the use of NAS rather than FAS when analyzing the aerobic capacity of animals.